2015
DOI: 10.1111/jphd.12130
|View full text |Cite
|
Sign up to set email alerts
|

Developing a flexible core Dental Public Health curriculum for predoctoral dental and dental hygiene schools

Abstract: Objective: The curriculum for graduating dental and dental hygiene students must prepare them to contribute to the improvement or maintenance of health for individual patient's and the public's health. The objective is to describe the background for and the process used to develop a core Dental Public Health Curriculum for such students. Methods: The process used was to solicit and review existing dental public health curriculum in dental and dental hygiene schools; review curriculum for other health professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…7 Our study found almost double the respondents (44%) had received some form of advocacy training at either the predoctoral or postdoctoral level, which is a very encouraging trend. 15 Our study found that those pediatric dentists who perceived a current need for advocacy training were less likely to have received training during their dental education years. Therefore, we rejected our hypothesis and concluded that there is a positive association between current willingness to advocate for CWF and prior advocacy training during dental education.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…7 Our study found almost double the respondents (44%) had received some form of advocacy training at either the predoctoral or postdoctoral level, which is a very encouraging trend. 15 Our study found that those pediatric dentists who perceived a current need for advocacy training were less likely to have received training during their dental education years. Therefore, we rejected our hypothesis and concluded that there is a positive association between current willingness to advocate for CWF and prior advocacy training during dental education.…”
Section: Discussionmentioning
confidence: 60%
“…8 In a recent study that developed competencies for predoctoral dental and dental hygiene programs, the authors concluded that advocacy is one of the important topics that can be integrated into predoctoral dental curricula to train general dentists to become better oral health advocates. 15 Our study found that those pediatric dentists who perceived a current need for advocacy training were less likely to have received training during their dental education years. This finding suggests that those perceiving a current need for advocacy training might not feel this way had they received training during their dental education.…”
Section: Discussionmentioning
confidence: 60%
“…Table reports the 23 DPH topics identified in the curriculum development phase on which AAPHD members were asked to review or pilot test. Responses from the 89 respondents indicated that members’ interest in pilot testing each of the specific topics ranged from 8 to 47 percent, depending on the topic.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Survey Monkey online portal, between April and May 2013, the survey was distributed to the AAPHD membership who had a working email in their association membership information. Members were asked: a) about their willingness to review and/or pilot test the developed DPH curriculum, and if willing, then b) on which of the 23 DPH topic(s) identified in early stages of the project were they willing to review and/or pilot test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation